The Relationship between Primary Energy Consumption, Energy Security Index, Share of Renewable Energy and the Energy Transition in Indonesia - Wahyudi, Heru; Awaluddin, Imam; Murwiati, Asih; Nirmala, Tiara; Leny, Sandra Mei; Rohman, Fatkhur (International Journal of Energy Economics and Policy, 2025)
Energy security and the transition to renewable energy are strategic issues in global energy policy, especially for developing countries that still face the challenge of dependence on fossil energy. Indonesia, as one of the countries with high primary energy consumption, has set a target of 23% renewable energy mix by 2025. However, the achievement is still far from the set target, indicating structural barriers in the energy transition. One of the key determinants in the energy transition is the Energy Security Index and primary energy consumption, which may have implications for the share of renewable energy in the national energy mix. Although various studies have explored the relationship between energy security and sustainable energy mix, empirical studies that comprehensively analyse the impact of Energy Security Index and primary energy consumption on the share of renewable energy in Indonesia are still limited. Therefore, this study aims to examine the relationship between the Energy Security Index, primary energy consumption, and the share of renewable energy and evaluate the extent to which the two independent variables affect the energy transition in Indonesia. This study uses a quantitative approach with the robust least squares method to produce more accurate parameter estimates. The results show that the energy security index has a positive and significant effect on the share of renewable energy, with a coefficient of 1.570 (0.0000 < 0.05), indicating that increased energy security contributes to the acceleration of the renewable energy transition. In contrast, primary energy consumption shows a negative impact on the share of renewable energy, with a coefficient of −3.802 (0.0433 < 0.05), indicating that dependence on fossil energy hinders the increase in the share of clean energy. In addition, the F-test shows that the Energy Security Index and primary energy consumption simultaneously have a significant influence on the share of renewable energy (0.0000 < 0.05), with a coefficient of determination R2 of 89.36%, indicating that the model used is able to explain most of the variability in the share of renewable energy. This finding confirms that improving energy security through energy source diversification and energy efficiency are key factors in accelerating the energy transition. The government needs to reduce dependence on fossil fuels and accelerate incentives for renewable energy so that the renewable energy mix target can be achieved.